ANAK DAN PERILAKU KONSUMTIF DI SURAKARTA (Kajian Budaya Konsumen) - Wangi, Maya Sekar (Transformasi, 2012)
Abstract Friendly consumer behavior triggered by a variety of factors. If the produksionis - a term for people who believe in the power of producer-regard children as passive consumers can be persuaded through advertising, the results of this study indicate that advertising is not always affect the consumption behavior of children. In addition to the child's behavior is characterized by the consumption of purchased impressions and experiences of activities undertaken through the meal, private ownership and use of leisure time. Â  Keyword: Behavior; Consumption; Child